2015
DOI: 10.1016/j.str.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The ssDNA Mutator APOBEC3A Is Regulated by Cooperative Dimerization

Abstract: Deaminase activity mediated by the human APOBEC3 family of proteins contributes to genomic instability and cancer. APOBEC3A is by far the most active in this family and can cause rapid cell death when overexpressed, but in general how the activity of APOBEC3s is regulated on a molecular level is unclear. In this study the biochemical and structural basis of APOBEC3A substrate binding and specificity is elucidated. We find that specific binding of single-stranded DNA is regulated by the cooperative dimerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
137
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(149 citation statements)
references
References 75 publications
11
137
1
Order By: Relevance
“…4, B and C). This improved activity relative to the A3Bctd-QM⌬loop3 parental construct is consistent with the more open active site conformation reported recently for A3A (34,40) (Fig. 3E).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4, B and C). This improved activity relative to the A3Bctd-QM⌬loop3 parental construct is consistent with the more open active site conformation reported recently for A3A (34,40) (Fig. 3E).…”
Section: Resultssupporting
confidence: 92%
“…As observed for the closely related Z1-type deaminase domains A3A and A3Gctd, ␤2 on the exposed edge of the ␤-sheet is interrupted by a short 3 10 helical segment (helix 1 in Fig. 2A; A3A (34,40); A3Gctd (30,31,33,37,39)). Correspondingly, the C-terminal end of ␣2, which interacts with this helical segment, is bent toward the discontinuous ␤2 (Fig.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Although the crystal structure study of A3A suggested a cooperative dimerization model for its action on DNA, the structural basis of A3A's RNA-editing and RNP complexforming abilities is still unknown (37,59).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies and atomic force microscopy observations showed that APOBEC3G (A3G) formed a dimer (34,35) or an oligomer (36). APOBEC3A (A3A) was very recently crystalized as a dimer (37). Also, the dimeric structure of APOBEC1 (A1) was suggested by biochemical studies (13,38,39).…”
Section: Detection Of Apobec Homodimer Formation By the Monomeric Kusmentioning
confidence: 99%